(untitled) (Raparin Journal of Humanities (RJH), 2023)
Human beings own an intelligent and conscious existence. This distinguishes human beings from other creatures. Human beings are characterized by thinking and asking questions about existence in general, their own existence and the universe. No other creatures possess such an intelligence. We ask why am I here and what is the source and nature of my existence? How did this world come into existence? and many other questions, which have become a problem and occupied the human mind. Before and after the rise of philosophy, the question of existence has been an important issue and an essential problem of all time. Consequently, man has been searching for the truth and answers to his questions. Man’s consciousness is imperfect, which has become the source of his desires for self-completion and perfection. This imperfection is an incentive for continuous efforts to comprehend the meaning of existence. Throughout the ages, philosophers have sought the nature of the question of existence according to the times in which they lived. The answers to this question have varied, each interpreting it in a different way. Plato interpreted the question of existence under the influence of a number of schools and philosophers. The absolute existence of the Elites became the basis of the idealistic theory of eternal change, in which Heraclitus’ philosophy became an important characteristic of the perceived world and material appearances, and benefited from Pythagorean numeracy. Plato’s theory of existence is similar to his theory of knowledge, in a way that rises from the senses to the mind, and divides existence into two parts on this basis: The presence of objects and the presence of consciousness. Plato presents his theory of the origin and creation of the universe, which can be called "Plato’s geometric nuclear or mathematical theory" about the nature of existence and the distinction between apparent existence and exemplary existence. In Plato’s view of absolute existence, the "idea" and the general existence is the existence from which all things in the world originate.